How Polarization and Political Instability affect Learning through Experimentation - Ioulia V. Ossokina; Otto H. Swank (Tinbergen Institute, 2001)
In a multiperiod setting, decision-makers can learn about the consequences of their decisions throughexperimentation. In this paper we examine how in a two-party system polarization and political instability affectlearning through experimentation. We distinguish two cases:the decision to be made is not salient and does notaffect the outcome of the following elections (exogenous elections) andthe decision is salient and the election outcome depends on it (endogenous elections).We show that while the possibility of learning increases activism,the existence of political instability distorts learning. Furthermore, in contrast to the existing literature, wedemonstrate that, when elections are exogenous, polarization between political parties does not always decreaseactive learning. In the case with endogenous elections we find that electoral concerns may induce candidates not toexperiment, even if the majority of voters prefers activism.
Keywords: D72; D82; 330; Active learning; Elections; Polarization; Test; Lernprozess; Theorie; Politische Stabilität; Politische Entscheidung